Relationships among the tethered 3-min all-out test, MAOD and swimming performance - Kalva-Filho, C. A.; Moura Zagatto, A.; da Silva, A. S. R.; Yndawe Castanho, M.; Bucken Gobbi, R.; Gobatto, C. A.; Papoti, M. (International Journal of Sports Medicine, 2017)
To allow the use of the 3-min all-out parameters for anaerobic evaluation, the aim of the present study was to test its relationships to maximal accumulated oxygen deficit (MAOD) and short/middle distance performances. 9 swimmers (age 19±1 years, height 176.7±6.1 cm and body mass 68.7±6.1 kg) underwent a 3-min all-out test and MAOD procedures (10 submaximal efforts and one exhaustive effort at maximal force attained during a graded exercise test); both were applied using tethered swimming conditions. Short/middle free-swimming performances were assessed at 50, 100 and 200?m distances. Only the peak force (PF) attained during 3-min all-out test exhibited a direct relationship to MAOD (r=0.77; p=0.02). Mean force, mean force until 150?s and total impulse, which were obtained during the 3-min all-out test, exhibited inverse relationship to short/middle performances (r>-0.79; p<0.02). However, no relationship was observed between PF and performances. In addition, MAOD exhibited an inverse relationships to all performances (r>-0.72; p<0.04). Thus, the present study demonstrated that only PF can be used to evaluate the anaerobic metabolism and most of the 3-min all-out test parameters are dependent on force maintenance capacity, which is also important in short/middle performance.